Biotechnological Innovations and Therapeutic Application of Pediococcus and Lactic Acid Bacteria: The Next-Generation Microorganism - Peter, Sunday Bulus; Qiao, Zhina; Godspower, Hero Nmeri; Ajeje, Samaila Boyi; Xu, Meijuan; Zhang, Xian; Yang, Taowei; Rao, Zhiming (Frontiers in Bioengineering and Biotechnology, 2022)
Lactic Acid Bacteria represent a worthwhile organism within the microbial consortium for the food sector, health and biotechnological applications. They tend to offer high stability to environmental conditions, with an indicated increase in product yield, alongside their moderate antimicrobial activity. Also, their lack of endotoxins and inclusion bodies, extracellular secretion, surface display with other unique properties, are all winning attributes of these gram-positive Lactic Acid Bacteria, of which, Pediococcus is progressively becoming an attractive and promising host, as the next-generation probiotic comparable to other well-known model systems. Here we presented the biotechnological developments in Pediococcal bacteriocin expression system, contemporary variegated models of Pediococcus and Lactic acid bacteria strains as microbial cell factory, most recent applications as possible live delivery vector for use as therapeutics, as well as, upsurging challenges and future perspective. With the radical introduction of Artificial intelligence and Neural network in Synthetic Biology, the microbial usage of Lactic Acid Bacteria as an alternative eco-friendly strain, with safe use properties compared to already known conventional strains is expected to see an increase in various food and biotechnological applications in years to come as it offers better hope of safety, accuracy and higher efficiency.